2010
DOI: 10.1007/s11033-010-0452-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional markers based molecular characterization and cloning of resistance gene analogs encoding NBS-LRR disease resistance proteins in finger millet (Eleusine coracana)

Abstract: Magnaporthe grisea, the blast fungus is one of the main pathological threats to finger millet crop worldwide. A systematic search for the blast resistance gene analogs was carried out, using functional molecular markers. Three-fourths of the recognition-dependent disease resistance genes (R-genes) identified in plants encodes nucleotide binding site (NBS) leucine-rich repeat (LRR) proteins. NBS-LRR homologs have only been isolated on a limited scale from Eleusine coracana. Genomic DNA sequences sharing homolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Identification of Fr genes themselves would obviate the need to use SNPs in linked genes as surrogates for marker assisted selection. In several plant systems, disease resistance genes have been molecularly identified and this creates useful tools for breeders to monitor their transmission to progeny [37][38][39][40][41]. Many of these resistance genes have been identified in genomic mapping studies, and as the loblolly pine draft genome continues to improve with additional information, integration of the genetic and physical maps around Fr loci should be feasible.…”
Section: Identifying Fr Genes: Paths Forwardmentioning
confidence: 99%
“…Identification of Fr genes themselves would obviate the need to use SNPs in linked genes as surrogates for marker assisted selection. In several plant systems, disease resistance genes have been molecularly identified and this creates useful tools for breeders to monitor their transmission to progeny [37][38][39][40][41]. Many of these resistance genes have been identified in genomic mapping studies, and as the loblolly pine draft genome continues to improve with additional information, integration of the genetic and physical maps around Fr loci should be feasible.…”
Section: Identifying Fr Genes: Paths Forwardmentioning
confidence: 99%
“…Since an array of genetic diversity for drought stress tolerance is available in small millets germplasm, systematic phenotyping and genotyping of germplasm challenged under field-level drought condition will be ideal for association and MAS studies. To develop molecular markers for MAS and breeding in finger millet for fungal blast disease resistance, Panwar et al (2011) have reported developing EST-based resistance gene analogue (RGA) markers. A comparative genomics approach was used to establish association of SSR markers to finger millet blast disease resistant QTL (Babu et al, 2014).…”
Section: A Molecular Marker Resources and Genetic Mapsmentioning
confidence: 99%
“…Such examples are the development of SNPbased FMM for SiDREB2 gene involved in dehydration response in foxtail millet (Lata & Prasad, 2013). The ESTbased SSR markers were developed for NBS-LRR R-gene in finger millet (Panwar et al, 2011) to screen blast resistance. Genome wide EST-SSRs were developed in pearl millet using available EST sequence information in the database (Senthilvel et al, 2008).…”
Section: Fmms For Agronomic Traitsmentioning
confidence: 99%